The Historicity of Ratib Al-Haddad Tradition and Its Relevance of Priority In The Covid-19 Pandemic - Moh. Ashif Fuadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2021)
One of the most popular wirid in Indonesia is Ratib al-Haddad. The practice is a collection of prayers arranged by Abdullah ibn Alawi al-Haddad taken of the Qur'an and hadith. In a pandemic situation, the practice becomes one that is recommended by some circles to be beread so that the pandemic outbreak immediately subsides. But many of the practitioners are not yet aware of its history and virtues, especially during the pandemic. This paper intends to study the history of the wirid from the beginning of writing and its virtues. Through the historical approach, the method literature review, and observation of the practice of the ratiban tradition, this paper will explain the historical studies and benefits of practicing wirid Ratib al-Haddad, which is sourced from the description of the book of syarah (explanatory) of the Ulama. The wirid was compiled by al-Haddad to avoid the chaos of akidah there was that time. In addition, there are eight virtues implied in the text wirid one of which avoids the outbreak so that no doubt if the practice is widely recommended and practi ced in the current situation of the Covid-19 pandemic. The influence of ratib al-Haddad practice can also be seen through the congregation of the Majelis Jum'at Pagi (MJP) Al-Khoirot, who stated more peace of mind after practicing the wirid so as to increase immunity.